Melody Ko and Carol Saline sign copies of "A Day in the Life of the American Woman" at the Andover Senior Center. Photo 011 - Tobin, Joanie (Tufts Archival Research Center, 2008)
Melody Ko and Carol Saline sign copies of "A Day in the Life of the American Woman" at the Andover Senior Center.